Meningkatkan Partisipasi Peserta Didik dengan Metode Group Investigation pada Kelas X-E SMA Negeri 01 Sukodadi - Nazrul Amri; Raden Roro Nanik Setyowati; Ta’alamal Ikhsan (Journal on Education, 2023)
The research aims to enhance student participation by implementing the Group Investigation method in the 2023 academic year at X E class of SMA Negeri 1 Sukodadi. It consists of two cycles that encompass four stages, namely planning, implementation, observation, and reflection. The participants of the study are 36 students from X E class of SMA Negeri 1 Sukodadi. Data collection is conducted through observation and interviews. Qualitative data analysis techniques, including data reduction, data presentation, and conclusion drawing or verification, are employed. The research findings demonstrate that the implementation of the Group Investigation teaching method can improve student participation in learning. The increase in student participation is evident from the observation results. In Cycle I, student participation using the Group Investigation method is measured through observation sheets. The learning outcomes reveal that 25 students achieved a good rating, while 11 students obtained a satisfactory rating in the first cycle. In the second cycle, out of the total of 36 students involved in the learning process, 7 students received an excellent rating, 26 students received a good rating, and 3 students received a satisfactory rating. Based on the observations conducted, it can be inferred that there has been an improvement in student participation from the first cycle to the second cycle..